1988
DOI: 10.1203/00006450-198806000-00018
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effectiveness of Cysteamine and Phosphocysteamine in Elevating Plasma Cysteamine Concentration and Decreasing Leukocyte Free Cystine in Nephropathic Cystinosis

Abstract: ABSTRACT. Cysteamine (B-mercaptoethylamine, MEA) is currently used to treat children with nephropathic cystinosis. In this study MEA was compared to phosphocysteamine (MEAP), a phosphorothioester that tastes and smells better than MEA, with respect to its ability to elevate plasma MEA and deplete leukocytes of cystine. Studies were performed in six children with nephropathic cystinosis ranging in age from 2 to 10 yr. After equimolar oral doses of either MEA or MEAP plasma cysteamine was determined at various t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 15 publications
(24 reference statements)
2
38
0
Order By: Relevance
“…Despite the evident pharmacokinetic data [10,11], many patients and even many physicians do not realize that 2-3 h extra night pause may cause a significant cystine accumulation. Our study demonstrates that the administration of the same daily cysteamine dose distributed equally during 24 h results in significantly lower morning PMN cystine content, compared to the "only wake-time" regimen, applied by the majority of the patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the evident pharmacokinetic data [10,11], many patients and even many physicians do not realize that 2-3 h extra night pause may cause a significant cystine accumulation. Our study demonstrates that the administration of the same daily cysteamine dose distributed equally during 24 h results in significantly lower morning PMN cystine content, compared to the "only wake-time" regimen, applied by the majority of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Because intracellular leukocytes' cystine content decreases to the minimal levels about 2 h after cysteamine ingestion and than returns to pre-dose levels 6 h after the drug intake, the adequate cysteamine dose regimen implies the administration of the drug every 6 h [10,11]. This dose regimen, however, is extremely difficult to follow, especially at night.…”
Section: Introductionmentioning
confidence: 97%
“…This is above the peak plasma cysteamine concentrations (48.6±10. 7 [SD] ,tM) obtained in the treatment ofcystinosis (27). However, in patients with frequent recurrent hemarthroses, e.g., ARC-10 and the patient reported by O'Brien and Tuddenham (28) and Gitschier et al (29), even a very small VIII:C increase might have a significant clinical benefit, and clinical trials will be necessary to evaluate the potential role of cysteamine in the management of FVIII-EH patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we noted a 62% leukocyte cystine depletion 90 min after an i.v. cysteamine dose of 10 mglkg; Smolin et al (18) found 62% depletion 1 h after a dose of 18 mglkg. With our patient serving as his own control, leukocyte cystine concentrations at their nadir (approximately 6 h after a dose) were virtually identical whether the dose was received i.v.…”
Section: Discussionmentioning
confidence: 99%
“…The therapy of nephropathic cystinosis, besides replacement of renal losses, involves treatment with the cystine-depleting agent, cysteamine (16), or its more palatable bioequivalent, phosphocysteamine (17,18). Cysteamine, given orally every 6 h at a dosage of 1.3-1.95 g/m2/day (60-90 mg of free base/ kglday), has proven remarkably efficacious in preventing renal glomerular deterioration (19), permitting improvement of renal function in children under age 3 (20), and enhancing somatic growth in preadolescent cystinosis patients (19,20).…”
mentioning
confidence: 99%